3G+7g=60

Simple and best practice solution for 3G+7g=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3G+7g=60 equation:


3g+7g=60

We simplify the equation to the form, which is simple to understand
3g+7g=60

We move all terms containing g to the left and all other terms to the right.
+3g+7g=+60

We simplify left and right side of the equation.
+10g=+60

We divide both sides of the equation by 10 to get g.
g=6

See similar equations:

| 0.8+2x=x+3.5 | | 8y-6y=-114 | | -28=-3b | | 2-3z=7z | | 5=9-x | | -9x-2=47 | | z+11=-15 | | 6b-8b=-22 | | =s^2+8s+20 | | 6+n=7*2 | | 3a+6a=27 | | r^2-11=0 | | 2=x/4 | | -5(x+3)=20 | | 5(b+7)=6b | | 11x+18-6x=3 | | 2+3(x-5)=4(x-1) | | 11a-(7a-5)=a-10 | | 4(a-5)=3a | | 3x+45+44-4x=0 | | 3(a+2)=4a | | 4x-9=7x-15 | | (5x+8)-(2x-9)=38 | | 8y+4=4y | | 9y-3=6y | | 9x+99+65-5x=0 | | x*1.55-2.82=x | | x*1.55-x=2.82 | | 3x+5=3x+15 | | 5(x-6)-8x=15 | | 2y^2+29y-15=0 | | u^2+3u+1=0 |

Equations solver categories